NAIL PSORIASIS AS A DIFFICULT-TO-TREAT AREA: COMPARATIVE EVIDENCE FOR IL-17 AND IL-23 INHIBITORS - Kujach, Aleksandra; Góralska, Julia; Popielarczyk, Melania; Napiórkowska, Katarzyna; Płaza, Dominik (International Journal of Innovative Technologies in Social Science, 2026)
Nail psoriasis is a frequent and clinically relevant manifestation of psoriasis, affecting a substantial proportion of patients with plaque psoriasis and psoriatic arthritis. Despite its limited anatomical extent, nail involvement may cause pain, functional impairment, occupational limitations, psychological distress, and reduced quality of life. It is also strongly associated with psoriatic arthritis, supporting the concept of the nail unit as part of a broader synovio-entheseal disease continuum. Treatment remains challenging because of the slow growth of the nail plate, limited penetration of topical therapies, frequent involvement of both the nail matrix and nail bed, and delayed clinical response compared with cutaneous plaques. Biologic agents targeting the IL-23/IL-17 axis have substantially changed the therapeutic landscape of nail psoriasis. IL-17 inhibitors, particularly ixekizumab, secukinumab, brodalumab, and bimekizumab, generally show rapid and robust improvement in nail outcomes, with several head-to-head and network meta-analytic data sets favoring ixekizumab or bimekizumab for complete nail clearance. IL-23 inhibitors, including guselkumab, risankizumab, and tildrakizumab, also demonstrate clinically meaningful nail improvement, often with favorable long-term safety and durability profiles. However, direct comparative evidence remains limited, heterogeneous, and frequently derived from post hoc analyses or nail subgroups within broader psoriasis or psoriatic arthritis trials. This review summarizes current evidence for IL-17 and IL-23 inhibitors in nail psoriasis, with emphasis on comparative efficacy, kinetics of response, safety, outcome measures, and clinical decision-making.